Emotional intelligence of nursing applicants and factors related to it: A cross-sectional study. (February 2020) - Talman, Kirsi; Hupli, Maija; Rankin, Robert; Engblom, Janne; Haavisto, Elina
Abstract: Background: Emotions influence patient care decisions and professional relationships. Emotional intelligence has been proven to predict nursing students' success in clinical practice and academic performance. Scarce amount of studies have assessed the emotional intelligence in the nursing student selection context. Objectives: To assess the emotional intelligence of applicants to undergraduate (bachelor level) nursing education and the factors related to it. Design: Cross-sectional quantitative study. Settings: The data collection took place in four Universities of Applied Sciences in October 2016. Participants: Participants were nursing applicants ( N = 529) who took part in the entrance exams of the four Universities. Overall, 430 applicants (response rate 81%, 75 males) gave permission to access their results for the study's purposes. Methods: The Rankein Scale measure of emotional intelligence was used. All of the nursing applicants undertook the same electronic entrance exam in supervised computer classrooms. Statistical analysis included the use of two independent samples tests to compare differences in emotional intelligence scores and ANCOVA models to investigate whether background variables explained the observed differences. Results: In this study, nursing applicants' level of emotional intelligence was found to be average (on a scale of below average, average, above average). However, total scores ranged between 102 and 160 (of 160). Approximately 4% of the applicants scored below the minimum score (<130) and therefore failed the emotional intelligence test. A statistically significant difference was found between the pass and fail groups in terms of the total score. Significant differences were also found in the three subscores and in the total score of admitted and not admitted applicants. Conclusions: Nursing applicants enter their studies with differing EI skills. This finding may have a major impact on how nursing students experience emotions during their studies. More research is needed to establish the use of EI in student selection context.